THE INFLUENCE OF MASTERY OF POWERPOINT ON THE LEARNING ACHIEVEMENT OF HIGH SCHOOL STUDENTS BIOLOGY - Mutmainna, Nurul; Rusdi, Hikmah; Nurhidayah (Indonesian Journal of Educational Technology, 2024)
This study aims to develop an interactive e-module based on microlearning for the Kapita Selekta Pendidikan course at the Faculty of Education, Universitas Negeri Makassar, in response to students' needs for more modern and interactive teaching materials. Using the ADDIE model, this research went through five stages: Analysis, Design, Development, Implementation, and Evaluation. Initial analysis results indicated a strong need for interactive and digitally accessible learning materials. Based on this, an e-module was designed, then developed using Canva, and integrated into a flipbook format through Heyzine to enhance accessibility. Validation by content and media experts showed that this e-module has a very high level of validity, and trial results demonstrated high practicality among students. The study concludes the importance of integrating technology into teaching materials to enhance student engagement and understanding of the learning content, showcasing the effectiveness of the e-module as a relevant and appealing learning tool in the context of higher education.